Analogia Entis and Indigenous Ontology: Interpreting Faot Kanaf of Atoni Pah Meto in the Light of Thomistic Metaphysics - Patricius Neonnub; Octovianus Kosat (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2025)
This study explores the metaphysical significance of faot kanaf — the sacred clan stone of the Atoni Pah Meto of West Timor — through the lens of Thomistic analogia entis (analogy of being). While anthropological accounts have highlighted the social and ecological functions of faot kanaf, its implicit ontology remains underexamined. Rooted in a participatory cosmology, faot kanaf mediates relationships among humans, ancestors, and divine powers, embodying permanence and vitality as symbolic perfections. Interpreting this symbolism through Thomistic categories of participation and analogy reveals structural convergences: both systems affirm that finite realities signify transcendent meaning without collapsing into identity. This analogical framework provides a hermeneutical bridge for intercultural theology, advancing a model of inculturation that respects cultural integrity while deepening metaphysical understanding. By retrieving the sacramental logic inherent in Atoni ritual life, the study argues for an expanded theology of culture grounded in the universality of analogical being. The findings suggest that faot kanaf functions as a signum analogicum, illustrating how indigenous symbols can illuminate and be illuminated by the principles of classical metaphysics.